A multicenter, single-arm study using a modified faricimab treat-and-extend regimen in patients with macular edema due to central retinal vein occlusion: RVOSTAR study design protocol - Mineo Kondo; Masahiko Shimura; Akitaka Tsujikawa; Yuki Muraoka; Takahiro Kogo; Yuki Akiyama; Yuki Hama; Jun Tsujimura; Keisuke Iwasaki; Motohiro Kamei (PLoS ONE, 2025)
Introduction Anti–vascular endothelial growth factor (anti-VEGF) agents are generally considered to be the first line of therapy for macular edema due to retinal vein occlusion (RVO-ME). However, current anti-VEGF treatment regimens in Japan are unable to maintain long-term vision improvement, particularly in patients with central RVO-ME (CRVO-ME). Faricimab is a dual angiopoietin-2/VEGF inhibitor approved for the treatment of RVO-ME in Japan. The RVOSTAR study is being conducted to evaluate the long-term maintenance of vision outcomes with faricimab using a modified treat-and-extend (T&E) regimen in treatment-naïve Japanese patients with CRVO-ME or hemi–RVO-ME (HRVO-ME) and to assess the factors affecting visual acuity and treatment intervals. Methods and design RVOSTAR (Japan Registry of Clinical Trials; jRCTs041250001) is an unmasked, single-arm, multicenter, prospective interventional study. Patients with CRVO-ME or HRVO-ME will 1) receive faricimab 6 mg every 4 weeks (≤6 injections) until ME is resolved; 2) be observed with no treatment until ME reoccurs, based on pre-specified central subfield thickness (CST) criteria; and then 3) be treated according to a T&E regimen up to 72 weeks, with dosing intervals based on time to relapse and adjusted by 4-week increments (minimum interval: every 4 weeks; maximum interval: no limit). Vision outcomes include best-corrected visual acuity (BCVA) and CST. The primary endpoint is the change from baseline in BCVA at week 72. Safety outcomes include ocular and non-ocular adverse events. Conclusion RVOSTAR will evaluate the long-term maintenance of vision outcomes with a modified faricimab T&E regimen in patients with CRVO-ME or HRVO-ME while reducing the burden associated with frequent injections. The findings from this study may help to optimize dosing frequency in clinical practice.